Effect of added copper oxide with zinc oxide prepared via hydrothermal method. (2022) - Arlina, A.; Ibrahim, Norfadhilah; Pao, Ter Teo; Jaafar, Hidayani; Abdullah, Nor Hakimin; Akmal, Syamsyir; Rahimie L., Muhamud
Abstract: In this paper, study on the effect of added copper oxide (CuO) with zinc oxide (ZnO) using hydrothermal method. The amount of CuO addition start at 0 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, and 4 wt% respectively. The characterization of the samples were used Scanning electron microscope (SEM), X-ray Diffraction method (XRD) and Ultraviolet–Visible (UV–Vis) Spectroscopy. SEM images showed CuO addition with ZnO exhibit nanorod to hexagonal nano-flower like grains. Then, XRD data peaks shows the ZnO nanostructure was successfully added with CuO and the crystallite structure for all samples. UV–Vis Spectroscopy reveal that the effect of CuO added with ZnO is opaque due to no photocatalytic activity except for the no additive. The additive of CuO improve on the morphology, structure but reduce the photocatalytic activity of the samples.